Electron beam welding study of grade 1 CP Titanium. (2018) - Gupta, R.K.; Anilkumar, V.; Xavier, X. Roshan; Ramkumar, P.
Abstract: Mechanical properties at room temperature as well as at cryogenic temperatures (77K, 20K) were evaluated on parent metal as well as electron beam weldments of α–Ti (commercially pure grade I) in this work. The strength of the weldment as well as parent metal increased with decrease in temperature. Weld efficiency >95% at all the temperatures (ambient, 77K, 20K) was observed. Microscopy revealed single phase α in parent metal, which transformed to widmanstatten martensitic structure with feathery morphology in the weld.Increase in dislocation density near the failure tip of tensile test specimen and presence of dimples were observed indicating ductile failure/ sufficient amount of ductility even at 20K.